Assessment of provided service quality in B2B market from the manufacturer´s perspective - Vlčková, Vladimíra; Podškubková, Lucie (TANGER, spol. s r.o., 2019)
The quality of provided services relating to the product is considered one of the most important elements of development and sustaining effective and successful relationships within supply systems and a key factor of corporate competitiveness in the B2B market. The paper deals with targeted literature review that is focused on current concept of customer services mainly in B2B market, as well as on the interpretation and definition of service quality and on the way of its assessment using INDSERV tool. On the basis of a comparison of the outcomes of a targeted literature review and an analysis of creation of supplier’s assessment by the a selected manufacturer of non-woven textiles for the automotive industry, the paper identifies the deciding criterions used for assessing service quality provided by suppliers from a manufacture´s perspective.
Hodnocení kvality poskytovaných služeb na B2B trhu z pohledu výrobce
Keywords: B2B market; non-woven textiles; service quality; INDSERV; Q-LanYs; B2B trh; netkané textilie; kvalita služeb; INDSERV; Q-LanYs